2016
DOI: 10.1080/23279095.2016.1157078
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning of complicated-mild to moderate traumatic brain injury patients with frontal contusions

Abstract: Executive dysfunctions are among the most prevalent neurobehavioral sequelae of traumatic brain injuries (TBIs). Using culturally validated tests from the Delis-Kaplan Executive Function System (D-KEFS: Trail Making, Verbal Fluency, Design Fluency, Sorting, Twenty Questions, and Tower) and the Behavioural Assessment of the Dysexecutive Syndrome (BADS: Rule Shift Cards, Key Search, and Modified Six Elements), the current study was the first to examine executive functioning in a group of Iranian TBI patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…A large number of clinical studies have reported TBI‐induced attention deficits in affected individuals. A recent study in adult patients with lateral prefrontal contusions reported significantly reduced attention capacities as compared to the patients with contusions located in other frontal areas and normal controls using culturally validated tests from the Delis‐Kaplan Executive Function System (Trail Making, Verbal Fluency, Design Fluency, Sorting, Twenty Questions, and Tower) . Significantly poorer attention capacity and slower information processing speed were observed in TBI patients who showed poorer outcomes (evaluated using the Glasgow Outcome Scale) compared to those who showed better outcomes .…”
Section: Introductionmentioning
confidence: 95%
“…A large number of clinical studies have reported TBI‐induced attention deficits in affected individuals. A recent study in adult patients with lateral prefrontal contusions reported significantly reduced attention capacities as compared to the patients with contusions located in other frontal areas and normal controls using culturally validated tests from the Delis‐Kaplan Executive Function System (Trail Making, Verbal Fluency, Design Fluency, Sorting, Twenty Questions, and Tower) . Significantly poorer attention capacity and slower information processing speed were observed in TBI patients who showed poorer outcomes (evaluated using the Glasgow Outcome Scale) compared to those who showed better outcomes .…”
Section: Introductionmentioning
confidence: 95%
“…Traumatic brain injury (TBI) is a global public health problem, causing significant mortality and morbidity worldwide [1]. Despite improvements in mortality rates achieved by ongoing advancements in healthcare, many survivors of TBI suffer with longstanding neuro-cognitive deficits that heavily impair their ability to function independently [2][3][4][5][6][7]. There is an unmet need for therapeutic interventions given that several pharmacological approaches to improve outcomes have remained unsuccessful to date [8].…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a global public health problem; predicted by the World Health Organisation (WHO) to become one of the leading causes of death and disability by the end of this year [ 1 , 2 ]. The best available medical and neurosurgical interventions reduce mortality rates after severe TBI, but a significant number of survivors are left with life changing moderate-to-severe disabilities [ 3 ]; the negative effects are largely related to sensory-motor, neuro-cognitive, behavioural and memory deficits [ 4 , 5 , 6 , 7 , 8 , 9 ]. From a pathophysiological standpoint, TBI causes significant neuronal cell death primarily in the cerebral cortex [ 10 ], largely evident during the secondary stages of host response to injury [ 11 ].…”
Section: Introductionmentioning
confidence: 99%